The new German energy policy: What role for gas in a de-carbonization policy? - Ralf Dickel (The Oxford Institute for Energy Studies, 2014)
German Energy policy - in its current form the Energiewende - is the product of a complex evolution of overt aspirations of many of the parties in and out of governing coalitions since the turn of the century, and a covert fear of import dependency on Russian gas combined with 'coal-mindedness' - an affinity for the use of coal and lignite, despite the country's net coal import position. In this extensive and comprehensive paper, Ralf Dickel explains the political path by which Germany's current energy policy was derived and in particular the way in which the Fukushima disaster on March 2011 finally catalysed an embedded desire to exit nuclear energy in many political factions to fulfilment through consensual legislation. Phased nuclear closure and a desire to achieve decarbonisation targets drove the many scenarios underpinning energy policy, but the role of gas was never explicitly addressed within the governing political mainstream. The choice between gas and coal/lignite was comprehensively 'ducked' but as the abject failure of the ETS system unfolded it was convenient to ascribe such a choice as being 'for the market to decide'. At present a CO2 price of exteuro50/tonne CO2 would be required to burn gas in favour of coal in German power plant. Looking ahead however, the paper anticipates potential developments for which the maintenance of the German gas sector and its transmission grid would be much more positive (preserving options) than allowing gas to wither and coal and lignite to maintain dominance. These include the continuation of biogas generation, gas with CCS (having superior investment economics than coal and lignite) and power to gas, via the Sabatier process, by which surplus renewable power generation could be stored as (zero carbon) gas and utilised by the existing transmission and storage system.
Keywords: 330; Energiepolitik; Treibhausgas-Emissionen; Deutschland